THE CONCEPT OF LEGAL CULTURE IN JURISPRUDENCE - Коба, Марія Миколаївна (Scientific works of Kyiv Aviation Institute. Series Law Journal "Air and Space Law", 2019)
Purpose: the article analyzes theoretical and legal problems of the concept of legal culture, reveals the main methodological approaches to its understanding. Research methods: in the work the dialectical method of cognition, general scientific and special-legal methods were used. A systematic method has been chosen as the main methodological method of cognition, which allowed to consider legal culture as a multidimensional phenomenon, which consists of many relatively stable elements, the unity of which forms the system and provides an opportunity to distinguish the legal culture from other legal phenomena. Results: the results of comprehension of the concept of legal culture in historical discourse and modern legal science are summarized. The essence of the most popular methodological approaches to the understanding of the legal culture: broad and narrow, material and spiritual; axiological and philosophical. It is revealed that the existing methodological approaches to the understanding of legal culture are related to the modern paradigm of law as a measure of freedom and justice. They cannot go beyond the existing basic theories of legal thinking - natural, normative, sociological, historical. It is proved that the methodological platform of modern domestic theoretical and legal studies of legal culture is the principles of human-centrism and humanism, which make it possible to consider the aforementioned notion in the axiological approach. The definition of legal culture as an integral part of the general culture, the set of factors characterizing the level of legal awareness, legal relations, perfection of legislation, organization of work on its observance, state of law and order are substantiated. The conclusion is reached: legal culture is a complex and multidimensional phenomenon, therefore the application of any one of the approaches to its understanding does not reveal its essence. The expediency of using an integrated approach, which integrates the most essential characteristics of the notion of legal culture, is substantiated. Discussion: the search for new rational ways of knowledge of the subject of legal culture and methods and methods for raising its level in modern conditions.